Analysing the factors affecting the incorporation of sustainable development into European Higher Education Institutions' curricula. (27th August 2019) - Lozano, Rodrigo; Barreiro‐Gen, Maria
Abstract: There has been an increase in sustainable development (SD) integration into Higher Education Institutions' (HEIs) curricula. Several tools have been developed to assess SD in HEIs; however, only a few have focussed on curricula assessment, such as the "Sustainability Tool for Assessing UNiversities' Curricula Holistically." Curricula assessment can provide an overview on how courses and programmes incorporate SD. This paper analyses the factors affecting the incorporation of SD in curricula using a survey sent to a database of 4, 099 European contacts, with a response rate of 9.85%. The responses were analysed using descriptive statistics, t test, ANOVA, and correlations. The analyses showed that (a) teaching in European courses covers many issues of sustainability in a fairly good balance, with the exception of social issues that are the least addressed; (b) there are correlations between the economic, environmental, social, and cross‐cutting themes; (c) females tend to teach SD in a more balanced way than men; (d) the HEIs types have no influence on how SD is being taught, but the education level has; and (e) some countries, in the case of this research, Italy and Spain, may show more interest, yet the average results tended to be lower than those others, in this research, Sweden, the United Kingdom, and the Netherlands. Curricula assessment provides a diagnostic of SD incorporation and the factors that affect it. This can help educators improve their courses and provide students with better SD skills and insights.